Opinion 2442: Cetonia marmorea Olivier, 1789 (currently Gymnetis marmorea; Coleoptera, Cetoniinae, Gymnetini): precedence granted over Scarabaeus pulcher Swederus, 1787 - ICZN (Bulletin of Zoological Nomenclature, 2019)
The International Commission on Zoological Nomenclature has conserved the specific name of Cetonia marmorea Olivier, 1789 (currently Gymnetis marmorea) by giving it precedence over its senior subjective synonym Scarabaeus pulcher Swederus, 1787.
Keywords: Nomenclature; taxonomy; Insecta; Coleoptera; Scarabaeidae; Cetoniinae; Cetonia marmorea; Gymnetis marmorea; Gymnetis pulchra; Gymnetosoma marmorea; Scarabaeus pulcher; Neotropics; flower chafer